Land Use and Cover Change in the Industrial Era: A Spatial Analysis of Alpine River Catchments and Fluvial Corridors - Hohensinner, Severin; Atzler, Ulrike; Berger, Monika; Bozzetta, Thomas; Höberth, Christian; Kofler, Martin; Rapottnig, Leena; Sterle, Yvonne; Haidvogl, Gertrud (Frontiers in Environmental Science, 2021)
Land uses affect flood risks in various ways. The comparative analysis of the historical and current land cover/uses helps to better understand changing flood regimes. Based on historical cadastre maps from 1826-1859, the land cover/uses in the Austrian catchments of the rivers Rhine, Salzach and Drava were reconstructed to almost the level of exact plots of land. Catchment-wide analysis reveals a six-fold expansion of settlement areas, a decline of arable land by 69 % and a shrinking of the formerly glaciated areas by 73 % until 2016. In the Alpine fluvial corridors, i.e. flood-prone areas at the valley floors and valley sides at ca. 300-year floods, settlements even expanded 7.5-fold, severely increasing the potential for flood damages. At the same time, the overall channel area of running waters has been reduced by one third and 95 % the formerly large wetlands have been lost. Overall, the fluvial corridors were truncated by 203 km² or 14 %, thereby reducing flood retention capacity. The concentration of intensive forms of human land uses at lower altitudes, coupled with an upward shift of less intensively used, near-natural forms of land cover, has led to a both spatial and vertical separation of Alpine landscape features over the long term. Warmer temperatures due to climate change are expected to promote the demonstrated upward shifts of Alpine vegetation.